Atmosfera controlada dinâmica monitorada pelo quociente respiratório e sua interação com estádios de maturação sobre a conservação da qualidade e o perfil volátil de maçãs galaxy - Thewes, Fabio Rodrigo (2016)
Harvesting the apple at the correct maturity stage for long-term storage is becoming more and more difficult, especially due to the lack of manual labor. Thereby, the development of storage techniques that allows the storage of fruit harvested outside the correct maturity is necessary. Thus, on the present dissertation we aimed to evaluate a new dynamic controlled atmosphere storage technique based on the lower oxygen limit (LOL) monitoring by the respiratory quotient (DCA-RQ) and compare it with controlled atmosphere (CA) and the combination of CA with 1-methylcyclopropene application (CA + 1-MCP) on the physical, chemical quality and volatile profile of Galaxy apple harvested in three maturity stages (unripe, ripe and overripe). Two chapters composed the dissertation: the first is directed to evaluate the metabolism, physical and chemical quality and the second to evaluate the metabolism and volatile profile. Fruit of the three maturity stages stored under DCA-RQ showed lower ACC oxidase enzyme activity, internal ethylene, ethylene production and respiration rate as compared to fruit stored under CA. The storage under DCA-RQ 1.3 resulted in similar quality keeping as compared to CA + 1-MCP. Lower mealiness incidence and flesh breakdown were observed in DCA-RQ and CA + 1-MCP stored fruit. Higher flesh firmness was verified in DCA-RQ 1.3, if fruit were harvested unripe, higher in CA + 1-MCP, DCA-RQ 1.3 and DCA-RQ 1.5 in ripe harvested fruit and higher in CA + 1-MCP overripe harvested apple. The storage under DCA-RQ 1.5 resulted in acetaldehyde, ethanol and ethyl acetate accumulation, but at a concentration that did not increase the electrolyte leakage and physiological disorders related to fermentation, like flesh breakdown. Oxygen lowering down to extremely low partial pressure, by the storage under DCA-RQ 1.5, resulted in fruit with higher volatile compounds concentration that composed the aroma, regardless the maturity stage, as compared to fruit stored under CA. Additionally, the volatile compounds increase was not only observed for ethyl esters, but also in characteristic Galaxy apple esters, like butyl acetate, hexyl acetate and 2-methylbutyl acetate. With the 1-MCP application was observed a reduction in the aroma production as compared to CA and not allowed the increment of esters concentration with the maturity advance, resulting in fruit with similar ester concentration on the three maturity stages. Taken in account the physical, chemical quality and the volatile compounds, the best storage conditions for all maturity stages follow this order: DCA-RQ 1.5 > DCA-RQ 1.3 > CA + 1-MCP > CA.